Comparison of patellar tendon versus hamstrings autografts for anterior cruciate ligament reconstruction in Indian population: A randomised control trial study() - Gupta, Prateek Ku (J Clin Orthop Trauma, 2019)
Disruption of anterior cruciate ligament (ACL) is a common ligamentous injury of the knee. The best choice of graft for reconstruction remains undecided. This prospective, randomized clinical trial aimed to compare clinical results of bone-patellar tendon-bone (BPTB) grafts and four-strand semitendinosus-gracilis (QHT) grafts for ACL reconstruction over a 1-year follow-up interval in Indian population. METHODS: 42 consecutive patients with ACL injury were recruited, by pick and draw method and allotted into two groups with 21 patients in each group. Group A patients underwent arthroscopic ACL reconstruction using BPTB graft while QHT autograft was used for patients in Group B. All the patients underwent standard ipsilateral arthroscopic ACL reconstruction procedure using a single incision, antero-medial (AM) portal technique for BPTB or the QHT autograft by a same surgeon. Patients were followed up regularly for a minimum period of 1 year. RESULTS: After one year, the Cincinnati score was 91 ± 4.117 in BPTB group and 89.29 ± 5.371 in QHT group (P = 0.282). There was no significant difference between the two groups in the mean scores with respect to pain, overall activity level and running in the Cincinnati score. None of the patients complained of the knee giving way. Similarly, at 1 year, the Lysholm score was 92.84 ± 2.630 and 90.55 ± 2.395 in the two groups respectively (P = 0.842). There were no episodes of locking or instability and there was no significant difference in the mean Lysholm scores regarding pain and squatting. CONCLUSION: There was no significant functional difference between the two grafts in terms of Lysholm and the Cincinnati score, anterior knee laxity and altered sensation over proximal leg. The patients with QHT groups performed better than BPTB functionally at 6 month so early return to sport is possible even with QHT autograft.